Drug development in pediatric oncology – challenges and opportunities – reflections from European regulators. (2nd September 2018) - Karres, Dominik; O'Connor, Daniel; Norga, Koen; Siapkara, Angeliki
ABSTRACT: Introduction: Ten years of the Paediatric Regulation in Europe has resulted in progress in drug development for children. Nonetheless, drug development remains a challenge, particularly in the area of pediatric oncology, as cited by the European Commission's 10-year Report published in 2017. Areas covered: In order to further improve the timely availability of novel medicines for children with cancer, further collaborative efforts are needed. Whilst the regulatory framework might present challenges, it provides key tools necessary to support pediatric drug development. Expert Opinion: It is the regulators together with all stakeholders who need to apply these tools by means of concerted, innovative, and inclusive ways of thinking in order to make it a true success. This requires all stakeholders to reflect on their individual responsibilities in this process, not only to create a level of understanding amongst each other but also to push their own boundaries and challenge established ways of thinking for the benefit of the patient, a principle which holds true for pediatric drug development in general. This paper reflects on these challenges and the opportunities for regulators and key stakeholders.